Warehouse layout Design in Manufacturing Industry - Tranggono; Nur Rahmawati; Kinanti Resmi Hayati (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2021)
Manufacturing companies spend a significant amount of time and money designing or redesigning their facilities. It is an extremely important function that must be addressed before products are produced. Manufacturing company’s common problem is that they do not have a pattern for placing goods in their warehouse. It leads to problems such as difficulties when taking the product from storage. With storage procedures like this, it can make long total distance for loading and unloading the goods. Dedicated storage policy where storage is done at a certain location according to the type of item needs to be made. The advantage of this method is ease in finding goods as the location can be tailored to the shape of the goods. The research results show an efficiency of the displacement distance of 4117 m, the initial layout distance of moving goods is 5740 m, while in the proposed layout it is 1622 m.